StMYB308L and its regulatory role in flavonoid biosynthesis pathways in potato - Juan Wu; Peijie Wang; Rui Xie; Hushuai Nie; Xiaojuan Wu; Yu Ma; Chunxing Lu; Enze Yang; Nan Li; Yanhong Ma (BMC Plant Biology)
Abstract Background The potato (Solanum tuberosum L.) is a globally significant tuber crop, and colored potatoes, as a unique cultivar of potato, have garnered considerable attention from scholars in recent years. Result StMYB308L, belonging to R2R3-MYB, is 804 bp in length and encodes 267 amino acids, which are locatized in the nucleus. The expression of StMYB308L could be regulated under GA3 and ethylene glycol treatment, and was more significant in purple potato tubers flesh under different temperature treatments. Over-expression StMYB308L transgenic potato and tobacco plants were obtained through genetic transformation. The stalks of transgenic potato was deepened in color, and the expression of key genes related to flavonoid synthesis, StCHS, StF3’5 H, StCHI and StDFR, was significantly increased. The petal color of transgenic tobacco was deepened, and the anthocyanin content, flavonoid content and total antioxidant capacity in trangenic petals were higher than those of wild-type tobacco. A total of 20,775 differentially expressed genes (DEGs) were obtained between transgenic tobacco and wild-type tobacco by transcriptomics, and they were mainly enriched in secondary metabolite synthesis, phytohormone signaling, starch and sucrose metabolism, phenylpropane biosynthesis, flavonoid biosynthesis and other pathways. Conclusions Further analysis indicated that overexpression of StMYB308L up-regulated the expression pattern of genes Nt4CLs, NtDFRs, NtANSs, and NtBZ1s, which involved in the flavonoids, anthocyanins, flavonoid and anthocyanin accumulation.